Training load, maturity timing and future national team selection in national youth basketball players - Arede, J.; Freitas, T. T.; Johnson, D.; Fernandes, J. F.; Williams, S.; Moran, J.; Leite, N. (Journal of Functional Morphology and Kinesiology, 2022)
Despite its importance to the management of training stress, monotony and recovery from exercise, training load has not been quantified during periods of intensity training in youths. This study aimed to (1) examine and quantify the training load (TL) in youth national team basketball players during a 2-week training camp according to maturity timing and (2) determine which parameters were related to under-18 (U18) national team selection. Twenty-nine U-16 national team basketball players underwent an anthropometric assessment to determine maturity timing. Players were categorised by maturity timing (early vs. average), whilst TL parameters during a 2-week training camp (i.e., 21 sessions) prior to FIBA U16 European Championship were used for group comparison and to predict future U-18 national team selection. The early-maturing players, who were taller and heavier (p < 0.05), experienced greater training strain in week 1 (p < 0.05) only. Irrespective of maturity timing, training loads in week 2 were predictive of onward selection for the U-18 national team. Conclusion: Based on present findings, practitioners are encouraged to develop their athletes` ability to tolerate high weekly loads, but also to be mindful that athletes` perceived exertion during national team training may be influenced by maturity timing.